Synthesis and Characterization of Novel Fluorinated Polyurethane Elastomer Based on 1,4-Bis(4-amino-2-trifluoformethyloxyphenyl)benzene - Xu, Wenzong; Zhang, Yingying; Hu, Yuan; Lu, Bo; Cai, Tongming (Asian Journal of Chemistry, 2012)
A novel chain extender was synthesized containing fluorine element 1,4-bis(4-amino-2- trifluoromethyloxyphenyl)benzene (BAFB). Then BAFB was used to prepare a series of fluorine containing polyurethane elastomers (FPUEs) with different fluorine contents. The structures and properties of FPUEs were measured by fourier transform infrared spectroscopy, thermogravimetric analysis, microscale combustion colorimeter (MCC), water absorption test and contact angle measurement. The results show fluorine was incorporated into the polyurethane chains through the reaction between BAFB and prepolymers. Fluorine containing polyurethane elastomers show a better hydrophobic property, lower surface tension and better thermal stability due to the introduction of fluorine. The surface tension of FPUEs decreases from 29.8-20.8 mN/ m with the F content increasing from 2.7-5.9 %. Furthermore, FPUEs also exhibit good flame resistance and the peak heat release rate (PHRR) of FPUE based on BAFB (466.2 W/g) is much lower than that of polyurethane elastomer without F element (537.2 W/g).